Heritage ++, a Spatial Computing approach to Heritage Conservation - Yamini Patankar; Camilla Tennenini; Rafael Bischof; Ishita Khatri; Ricardo Maia Avelino; Wenqian Yang; Nijat Mahamaliyev; Fabio Scotto; Daniela Mitterberger; Bernd Bickel; Fred Girardet; Christophe Amsler; et al. (RILEM Technical Letters)
Historic structures are affected by numerous degradation processes driven by a complex system of interconnected and mutually influencing factors. Preserving these monuments is a multidisciplinary endeavour that extends beyond one-time interventions, necessitating a comprehensive methodology that involves various stakeholders, expert consultations, monitoring tools, and impact assessments. Limitations arise due to communication barriers and difficulty in translating and transferring experience among disciplines, often compromising the collective ability to define the best possible conservation strategies.